Prevalence and early-life risk factors of asthma in preterm adolescents: a cohort study - van Dokkum, Nienke H.; Bos, Arend F.; Reijneveld, Sijmen A.; Vrijlandt, Elianne J. L. E. (Frontiers in Pediatrics, 2026)
AimWe seek to elucidate the prevalence, types of respiratory symptoms experienced, and potential early-life risk factors of asthma in adolescence.MethodsWe performed a prospective cohort study including 294 adolescents [130 moderately-late preterm (MLP), 81 early preterm (EP), and 83 full-term (FT)]. Asthma, asthma-like symptoms, and smoking in early childhood and adolescence were self-reported. We collected prenatal and postnatal characteristics, including maternal smoking, bronchopulmonary dysplasia, and respiratory syncytial virus (RSV) infections.ResultsIn 11% of EP, 4% of MLP, and 4% of FT adolescents, a formal asthma diagnosis was made. Asthma-like symptoms were reported in 14%, 14%, and 7% of the cases, respectively. Being hospitalized for an RSV infection was associated with a four times higher risk of asthma in adolescence (odds ratio 3.68 and 95% confidence interval 1.04–13.0), while other predictors did not contribute.ConclusionMLP adolescents have similar rates of asthma and asthma-like symptoms as their FT peers, while EP adolescents might have a higher risk of asthma but have similar rates of asthma-like symptoms. RSV infections that require hospitalization are associated with an asthma diagnosis in adolescence.Clinical Trial Registrationhttps://www.controlled-trials.com, identifier ISRCTN 80622320.